2009
DOI: 10.1007/s10201-009-0290-8
|View full text |Cite
|
Sign up to set email alerts
|

Lateral input of particulate organic matter from bank slopes surpasses direct litter fall in the uppermost reaches of a headwater stream in Hokkaido, Japan

Abstract: In forested streams, surrounding riparian forests provide essential supplies of organic matter to aquatic ecosystems. We focused on two pathways of particulate organic matter inputs: direct input from upper riparian forests and indirect lateral input from bank slopes, for which there are limited quantitative data. We investigated the inputs of coarse particulate organic matter (CPOM) and carbon and nitrogen in the CPOM into the uppermost reaches of a headwater stream with steep bank slopes in Hokkaido, Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
1
13
0
8
Order By: Relevance
“…and litter characteristics, understanding of which may require specific experimental studies 8 . Moreover, as many environmental factors can affect lateral litter transport, it is not surprising that a range of lateral litter contributions have been reported, from negligible amounts to even surpassing litterfall contributions (e.g., in mixed-hardwood forest 9 ; in tropical rainforests 12 ; in tropical savanna 13 ; and in broadleaf forests 56 ). These findings are supported by the higher variability of lateral litter inputs observed at smaller scales (86% of total at sampling sites or samplers), which suggest that local factors (e.g., riparian density, ground complexity, stream bank slope and litter characteristics) are more important than regional ones in driving its dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…and litter characteristics, understanding of which may require specific experimental studies 8 . Moreover, as many environmental factors can affect lateral litter transport, it is not surprising that a range of lateral litter contributions have been reported, from negligible amounts to even surpassing litterfall contributions (e.g., in mixed-hardwood forest 9 ; in tropical rainforests 12 ; in tropical savanna 13 ; and in broadleaf forests 56 ). These findings are supported by the higher variability of lateral litter inputs observed at smaller scales (86% of total at sampling sites or samplers), which suggest that local factors (e.g., riparian density, ground complexity, stream bank slope and litter characteristics) are more important than regional ones in driving its dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…We observed increases of all sediment OM fractions and soil labile OM during high-flow period in RS, indicating that it is the period of greatest deposition probably due to the major OM particulate input from vegetation residues falling into streams (Kochi et al 2010). Conversely, study sites' downstream anthropogenic sources present a reversed pattern: more sediment deposition during low-flow period.…”
Section: Effect Of Flow Variationsmentioning
confidence: 72%
“…Due to the low primary productivity of rivers, the major input of organic matter is allochthonous (Artigas et al 2009;Kochi et al 2010). Accordingly, in undisturbed environments the main sources of organic compounds are cellulose and lignin from riparian vegetation (Wallis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, bank slope gradients ranged from 6.0°to 18.5°at the three streams. Kochi et al (2010) reported that lateral litter input surpassed the direct input at streams with [45°bank slopes, whereas Kochi et al (2004) reported that direct leaf-litter input was larger than lateral input at 14°bank slopes. In the present study, the dominance of vertical over lateral inputs at the three streams was probably due to the gentle bank slopes (maximum of 18.5°) at these streams.…”
Section: Discussionmentioning
confidence: 93%
“…Vertical and lateral inputs were converted into an area basis per month (g m -2 month -1 ), and lateral inputs were multiplied by two (two stream sides) and divided by the average stream width (e.g., Kochi et al, 2010). To compare the seasonality change between deciduous broadleaf and sugi needle, three seasons were defined, correspondent to the variation in deciduous foliage: (i) leaf-falling season (leaf fall in October and November), (ii) dormant season (no leaves in the crown until the formation of new leaves from December to April), and (iii) foliated season (green leaves in the crown from May to September).…”
Section: Seasonal Changes In Leaf-litter Input To Streamsmentioning
confidence: 99%